Clinician’s Guide to Prevention and Treatment of Osteoporosis - Cosman, F. (Springer London, 2014)
The Clinician’s Guide to Prevention and Treatment of Osteoporosis was developed by an expert committee of the National Osteoporosis Foundation (NOF) in collaboration with a multispecialty council of medical experts in the field of bone health convened by NOF. Readers are urged to consult current prescribing information on any drug, device, or procedure discussed in this publication.